Successful Brace Treatment of Pectus Carinatum in Osteogenesis Imperfecta Using the Dynamic Compression System - Orrick, Beth A.; Pierce, Amy L.; Snyder, Charles L.; Alon, Uri S. (European Journal of Pediatric Surgery Reports, 2019)
Osteogenesis imperfecta (OI) is a genetic disorder of collagen resulting in a “fragile” skeleton with increased fracture risk and other complications, dependent on the specific variant. Pectus deformities of the chest wall, while not common, can be associated with OI. The use of a pectus carinatum brace in a patient with OI poses unknown risks for fractures and adverse treatment outcomes. We successfully applied external compression bracing using the dynamic compression system to one such patient. This case illustrates the ability to treat an OI patient with pectus carinatum using a nonsurgical brace, without complications, resulting in an excellent cosmetic result.
Keywords: pectus carinatum; osteogenesis imperfecta; dynamic compression system